Business Disputes in Electronic Transactions Policy in Indonesia - Aloysius Wisnubroto; Dinda Aprilia (Faculty of Law, Universitas Pekalongan, 2024)
Economic activities conducted through internet-basedplatforms are generally referred to as electronic commerce (ecommerce). E-commerce offers significant advantages,particularly in terms of efficiency and convenience for bothconsumers and business actors. For consumers, e-commerceprovides ease of access to transactions without requiringphysical meetings, while for sellers, it reduces operationalcosts. However, despite these advantages, e-commerce alsoraises potential risks, particularly concerning the protectionof consumer rights, which may lead to disputes betweenconsumers and business actors. Consequently, the need foreffective and efficient mechanisms for dispute resolution ine-commerce transactions becomes imperative. Based on thisbackground, the research problem was formulated asfollows: How can business disputes in e-commerce beresolved based on the value of justice? To address thisquestion, the researchers employed a constructivistparadigm. The research design adopted was descriptiveanalytical, using a socio-legal approach. A socio-legalstudy integrates doctrinal legal analysis with insightsfrom social sciences. The data utilized in this studyconsisted of both primary data, collected through fieldresearch and interviews, and secondary data, obtainedfrom relevant literature and legal documents. Dataanalysis was carried out using qualitative descriptivetechniques. The findings of the research indicate thatonline arbitration represents a highly appropriatemechanism for resolving e-commerce disputes. This isdue to the inherent characteristics of e-commerce,which transcends geographical boundaries and allowstransactions to occur globally through internetconnectivity. In Indonesia, the legal frameworkgoverning e-commerce is primarily established underLaw No. 11 of 2008 on Information and ElectronicTransactions and Law No. 7 of 2014, particularlyChapter VIII concerning trade conducted throughelectronic systems. Nevertheless, the currentregulation on arbitration, namely Law No. 30 of 1999,remains limited to conventional arbitration and doesnot adequately address the unique challenges posed byonline dispute resolution. Therefore, it is crucial for thegovernment to formulate and enact new regulationsspecifically governing online arbitration as a disputesettlement mechanism in e-commerce. Such legal reforms are essential to ensure that dispute resolutionprocesses remain relevant and responsive to the rapidtechnological advancements shaping modern economicactivities. In this context, appropriate, clear, andenforceable legal measures are necessary to safeguardboth business actors and consumers, while promotingjustice and legal certainty in the digital economy.